Differential Interaction of Platelet-Derived Extracellular Vesicles With Circulating Immune Cells: Roles of TAM Receptors, CD11b, and Phosphatidylserine - Fendl, Birgit; Eichhorn, Tanja; Weiss, René; Tripisciano, Carla; Spittler, Andreas; Fischer, Michael B.; Weber, Viktoria (Frontiers in Immunology, 2018)
Secretion and exchange of biomolecules by extracellular vesicles (EVs) are crucial in intercellular communication and enable cells to adapt to alterations in their microenvironment. EVs are involved in a variety of cellular processes under physiological conditions as well as in pathological settings. In particular, they exert profound effects on the innate immune system, and thereby are also capable of modulating adaptive immunity. The mechanisms underlying their interaction with their recipient cells, particularly their preferential association with monocytes and granulocytes in the circulation, however, remain to be further clarified. Surface molecules exposed on EVs are likely to mediate immune recognition and EV uptake by their recipient cells. Here, we investigated the involvement of Tyro3, Axl, and Mer (TAM) tyrosine kinase receptors and of integrin CD11b in the binding of platelet-derived EVs, constituting the large majority of circulating EVs, to immune cells in the circulation. Flow cytometry and Western Blotting demonstrated a differential expression of TAM receptors and CD11b on monocytes, granulocytes, and lymphocytes, as well as on monocyte subsets. Of the TAM receptors, only Axl and Mer were detected at low levels on monocytes and granulocytes, but not on lymphocytes. Likewise, CD11b was present on circulating monocytes and granulocytes, but remained undetectable on lymphocytes. Differentiation of monocytes into classical, intermediate, and non-classical monocyte subsets revealed distinct expression patterns of Mer and activated CD11b. Co-incubation of isolated monocytes and granulocytes with platelet-derived EVs showed that the binding of EVs to immune cells was dependent on Ca++. Our data do not support a particular role for TAM receptors or for activated CD11b in the association of platelet-derived EVs with monocytes and granulocytes in the circulation, as anti-TAM antibodies did not interfere with EV binding to isolated immune cells, as binding was not dependent on the presence of TIM4 acting synergistically with TAM receptors, and as neither low levels of Gas6, required as a linker between phosphatidylserine (PS) on the EV surface and TAM receptors on immune cells, nor masking of PS on the EV surface did interfere with EV binding.